Role of a medical device for intra-vaginal use in improving the quality of the colposcopic examination and the anatomical/pathological reading of the cytological test and biopsy - Di Pierro, Francesco; Di Paola, Gaetana; Risso, Paolo (Acta Biomedica Atenei Parmensis, 2014)
To evaluate the efficacy of a vaginal suppository in overcoming unsatisfactory colposcopy and/or possible change in terms of diagnosis in women who have had abnormal cervical cytology, 98 females were enrolled and treated for 10 days with Kramegin®, a vaginal product in tablets containing Lactobacillus acidophilus, lactic acid and Krameria triandra extract. Seventy-eight of 98 females completed the study. Seventy-fife of 78 volunteers served for the statistical analysis. According to the results got, diagnoses were modified in almost 62% of cases; cervical conization was reduced in 58% of cases; regression for HSIL (to LSIL) was 35% higher than expected; need of follow-up decreased by 36% and treatment was well tolerated in about 96% of cases. Use of Kramegin® before colposcopy can be considered a good tool to increase the possibility of turning unsatisfactory colposcopy into satisfactory and seems to indicate a possible role in reducing cervical lesion progression. Deeper clinical investigations are mandatory to confirm this possible result